Polemik Hukuman Mati Di Arab Saudi Dalam Tinjauan Hukum Hak Asasi Manusia - Iqbal, Firdaus Muhamad (Law Study Program, Faculty of Law, Nusantara Islamic University, 2023)
The capital punishment is one of the world's oldest and most severe penalties, putting a person's life to death. Saudi Arabia is a country that allows and enforces capital punishment. Saudi Arabia's constitution incorporates the Qur'an and Sunnah and declares that the state defends human rights in line with Islamic Sharia, making it the only country with a legal system distinct from the rest of the world. This research applies normative juridical method. The instruments that contain the ban of the death penalty are described in this study. According to the findings of this study, there are treaties that ban the capital punishment, such as the Universal Declaration of Human Rights, the International Covenant on Civil and Political Rights and the Second Optional Protocol to the International Covenant on Civil and Political Rights. Capital punishment has always been a controversial subject since many parties oppose it. Nevertheless, Saudi Arabia, continues to implement the death penalty on its locals and foreign residents.